Analysis of The Effect of Unemployment Rate and Human Development Index On Poverty In The Province of North Sumatra - Marpaung, Riky Aulia Rachman; Rahayu, Fitri; Sintia, Iin (Outline Publisher, 2022)
This study aims to determine the effect of the Open Unemployment Rate and Human Development Index on poverty in North Sumatra. The data used is secondary data taken from BPS on the open unemployment rate, human development index, and poverty percentage. Data was obtained from panel data from 33 districts/cities in North Sumatra for 3 years from 2020 to 2022. The data analysis technique uses regression analysis using Random Effect based on the results of the Lagrange Multiplier test. The results showed that the open unemployment rate had a negative and insignificant effect on poverty. Meanwhile, the human development index has a negative and significant effect on poverty in North Sumatra.